Long-term compositional/microstructural development of Cr3C2-NiCr coatings at 500 °C, 700 °C and 900 °C. (September 2016) - Matthews, S.; Berger, L.-M.
Abstract: Cr3 C2 -NiCr thermal spray coatings are widely used to mitigate wear at temperatures between 500 and 900 °C. During deposition, compositional changes occur in the coating material. With exposure at elevated temperature the metastable as-sprayed structure begins to transform back to an equilibrium composition. The aim of this work was to determine the effect of heat treatment temperature on the mechanisms and rate of coating development at 500–900 °C for up to 30 days. Compositional development was characterised by X-ray diffraction. Image analysis was used to study the mechanisms of microstructure development and quantify the rate of carbide grain growth. Rapid transformation of the metastable coating phases to an equilibrium composition of Cr3 C2 and a Ni alloy occurred within 1–5 days at 500 °C and within 1 day at higher temperatures. The steady state composition matched that of the starting powder. The effect of the compositional/microstructural development on the coating microhardness is discussed. Highlights: In-flight carbide dissolution generated a metastable Ni binder and (Cr, Ni)7 C3 . The composition returned to equilibrium after 1–5 days at 500 °C. The composition returned to equilibrium within 1 day at 700 °C/900 °C. The rate, mechanism and extent of carbide development were temperature dependent. Coating microhardness development as a function of temperature is discussed.